Benefits, Challenges and Ethical Implications of Using Artificial Intelligence in Learning Psychological Concepts and Practices - Eugene Kwarteng-Nantwi; Benedicta Ama Adom-Mensah; Frank Baidoo; Pious Jojo Adu-Akoh, (African Journal of Education,Science and Technology (AJEST), 2025)
In Ghana, artificial intelligence (AI) is an emerging technology for students. This study explored the benefits, challenges and ethical implications of using of AI among undergraduate psychology students in the University of Cape Coast, Ghana. The study involved a descriptive survey of 148 participants. The study employed a structured questionnaire in 3 dimensions: benefits, challenges and ethical implications in using AI in learning psychological concepts and practices. The results revealed that students perceive AI as beneficial to their learning and use of psychological concepts. Also, the study revealed that students perceived some challenges with the use of AI in learning psychology and psychological concepts. Finally, the study showed that students perceive there exists some ethical implications in using AI in learning and psychological concepts. The study recommends that educational institutions should work towards improving access to AI tools for psychology students by integrating them into learning management systems, providing institutional licenses, or offering training on free or open-source alternatives. Furthermore, the study recommends AI developers should establish clear policies and guidelines regarding data privacy and security. Strict regulations should be implemented to protect user information, and students should be educated on ethical AI usage to minimize risks associated with bias and confidentiality breaches.